Cooperative Online Submission: Business Analysis and a Workflow Model - (:unkn) unknown (IEEE COMPUTER SOC, 2008)
Online Submission System allows articles to be submitted via the internet. We have brought a new approach to optimize peer review process and have integrated it to online submission system. The main objective of Online Submission System project is to enable users to submit their manuscript, or carry out a review on an assigned manuscript, over the Internet and in a professional way. In this article online submission processes will be explained in detail first and then mentioned generally the main structure that includes different types of users such as readers, authors, editors, section editors, chief editor and reviewers. In this model will be basically operated individual control panels.